Maximizing Segmentation for Promotion on Instagram - Farah Putri Wenang Lusianingrum; Fadhilah Fadhilah; Titis Nistia Sari (MOVE: Journal of Community Service and Engagement, 2022)
Only 4,000 MSMEs are active in Serang City from the initial 14,238 businesses due to the Covid-19 pandemic. The big challenge faced by micro-enterprises is marketing, especially digital promotion. Even though this micro business is a new or pioneering business, that still has to build branding and awareness through social media. Training with a demonstration approach that takes the theme of Maximizing Segmentation in Promotion on Instagram is considered helpful for overcoming existing problems. The training participants are ten micro-enterprises assisted by the “Rumah BUMN” of Bank BRI Serang City, which has yet to maximize social media. This training succeeded in increasing the 38 percentage of participants' understanding and knowledge regarding segmentation for promotion on Instagram.